Strategies of Pomatoschistus minutus and Pomatoschistus microps to cope with environmental instability - Dolbeth, M. (2007)
The populations of Pomatoschistus minutus and Pomatoschistus microps were studied from June 2003 to May 2006 in the Mondego estuary, in order to understand the ability of these species to withstand environmental variability. During this period a severe drought occurred (2005), with consequent lower freshwater runoff and higher salinity incursion into the estuary. Occasional abnormal high water temperatures were observed in 2003 and 2005. The fish populations were sampled monthly along an estuarine gradient, from which population density, structure, growth and biomass production was assessed. Pomatoschistus minutus distributed mainly at the most saline downstream area, while P. microps distributed within the whole estuary, in accordance to the salinity and temperature tolerances for the species. A clear decrease in density and production was observed for P. minutus in the dry year, with non-expressive recruitments and the quick disappearance of the parental cohort. For P. microps, the decrease was not so pronounced. No direct effects were attributable to the salinity and temperatures variations (resulting from the drought and high temperatures). Yet, higher predation pressure on P. minutus hypothesis was raised, as the salinity incursion increased the piscivorous marine adventitious species in the downstream areas. Pomatoschistus microps benefited from a wider temperature and salinity range tolerance, allowing the species to occupy different areas in the estuary and by this seemed better able to cope with the environmental conditionings during the 3-year studied period.